Analisis Penerimaan Dan Penggunaan Sistem Informasi Akademik Melalui Pengembangan Model Utaut Studi Pada Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Ponorogo - Wira Bharata; Premi Wahyu Widyaningrum (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
The need for an integrated academic information system is being increase, especially at the university level. The academic information system that will be created must be balance between the technology infrastructure availability and human resource capability. The purpose of this study is to measure the influence of academic information utilization system on the acceptance of users, especially the students of the University of Muhammadiyah Ponorogo. Another purpose of this study is to prove that the application of science and technology have been done well. This research is conducted at University of Muhammadiyah Ponorogo. The sample is the students who have used the academic information system at least one year. The sampling technique is stratified random sampling method with a sample size of 114 people. The data is analyzed using GSCA analysis tool. This research adopts UTAUT model developed by Venkatesh. The results is a positive relationship of each variable measured.